2022
DOI: 10.29133/yyutbd.1094883
|View full text |Cite
|
Sign up to set email alerts
|

Commercialization of Bambara Nut Production in Nigeria

Abstract: The global population increases daily, which requires a considerable increase in food production. Bambara nut is an important staple food crop capable of supplying essential nutrients to the body and providing the farmers with income, yet it is underutilized. This study, therefore, assessed the commercialization of Bambara nut production in Nigeria to enhance food availability. Primary data were gathered from 240 respondents and analysed using descriptive statistics, household commercialization index (HCI), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…This may explain why access to credit has a significant positive effect on the commercialization of pigeon pea production. This supports Falola et al (2022a), who recently reported that access to credit positively influences household commercialization. Distance to the market had a significant but negative effect on the commercialization of pigeon pea (P < 0.01).…”
Section: Determinants Of Commercialization Of Pigeon Pea Productionsupporting
confidence: 86%
See 2 more Smart Citations
“…This may explain why access to credit has a significant positive effect on the commercialization of pigeon pea production. This supports Falola et al (2022a), who recently reported that access to credit positively influences household commercialization. Distance to the market had a significant but negative effect on the commercialization of pigeon pea (P < 0.01).…”
Section: Determinants Of Commercialization Of Pigeon Pea Productionsupporting
confidence: 86%
“…The HCI is the ratio of the gross value of farm products sold to the value of the ones produced (Onyebinama, 2012;Falola et al, 2022a). It shows the extent to which a producer is commercialization-oriented, with a value ranging between 0 and 1.…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests the availability of a larger household size, which was employed as family labour in melon processing, thereby reducing the cost of processing melon. A larger household size increases the probability of getting physical assistance from family members, which enhances the proliferation of a venture (Falola et al, 2022b;Gbigbi, 2021;. Regarding their educational status, more than half of the respondents had primary education while a few had tertiary education.…”
Section: Demographic and Institutional Characteristics Of Women Melon...mentioning
confidence: 99%
“…Due to the capital involved in getting organic manure, high-income farmers used more organic manure than their counterparts with low incomes. This is because farmers' income determines the level of agricultural investment (Falola et al 2022a). Farm distance also had a positive influence on using organic manure.…”
Section: Drivers Of the Types Of Organic Farming Used By The Farmersmentioning
confidence: 99%